Influence of polyethylene oxide content on some characteristics of PLA/CS films loading nifedipine - Chinh, Nguyen Thuy; Nguyen, Trang Thi Thu; Mai, Tran Thi; Cong, Do Van; Huynh, Mai Duc; Trung, Tran Huu; Thang, Vu Viet; Hoang, Thai; Giang, Nguyen Vu (Vietnam Journal of Science and Technology, 2017)
This work mentions the effect of polyethylene oxide (PEO) content on some characteristics and properties of polylactic acid (PLA)/chitosan (CS) films loading nifedipine (NIF). The water contact angle, droplet size values and Field Emission Scanning Electron Microscopy (FESEM) images of the films are used to investigate their morphology and hydrophobicity. The obtained results show that the hydrophobic property of the PLA/CS/NIF films is improved by the presence of PEO. Besides, the PLA/CS/NIF films containing PEO have tighter structure and water absorbed ability less than those of the PLA/CS/NIF films